BlackBerry for Work - Mittal, Kunal (Apress, 2012)
Setting out to write my first technical book, I was skeptical of my ability to reach out to you in the simplest manner possible. With the backing of experienced editors and a co-author like I have had, I feel I have achieved that and more. We have tackled the subject to give you a basic understanding and clarity, thus reducing the factors that leave a novice lost. In this book, you will find many tips that will help enhance the BlackBerry experience considerably, and that is something which is always welcome now, isn’t it? My approach to the book has been simple. If I enjoy writing it, you will enjoy reading it. The language and style has been kept casual, conversational, and fiercely honest; these are also the factors that set this book apart from other user manuals available. From the contents of the book, you will notice that the matter covered spreads across a wide spectrum. From synchronization and configuration to downloading and usage, this book has a little something to offer to all professionals. At this point, I would also like to mention a by-product of the book that has now come to mean as much as the book itself. We, Shikha Gupta and Kunal Mittal, the co-authors have decided to direct all proceeds to a charity in India. The Mitr Foundation is a trust founded in the city of Hyderabad, with the objective of contributing its might towards the empowerment of the girl child through education. Thus, we have pledged to undertake the responsibility of educating three children. Somewhere between the elite and the underprivileged lies the core essence of our endeavor…for what is a life that is lived selfishly? I cannot promise that this book will be your best buy. But I can assure you that it will not disappoint either—neither in its content, nor in its philosophy. With hope that lives and dreams to share…